Kingdom of the Netherlands-Netherlands : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The strong output growth and labor market performance of recent years reflect both supply-side and demand-side factors. Fiscal restraint has a crucial role to play in containing the risk of further overheating, as well as in a medium-term perspective. Steady gains have been made in labor markets. The elimination of very high average and marginal tax rates is fundamental to further gains in labor market performance. Progress in liberalization of product markets has continued, but the momentum for reform needs to be maintained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet